ANALISIS PERBEDAAN STRESS DAN KELELAHAN KERJA BERDASARKAN SHIFT (STUDI KASUS PADA KARYAWAN ALFAMART TANGSI) - Mochamad Ilham Aziz; Ade Momon; Risma Fitriani (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2022)
Work-related activities and exposures make the body susceptible to exhaustion. Fatigue is the body's response to work-related activities and exposures. Psychosocial dangers, essentially job stress with symptoms such as frequent yawning, tiredness, thirst, and difficulties concentrating, are the general response to the high intensity of work. Typically, a job is scheduled in shifts, seasonal employment, weekend work, and overtime, which causes workers to experience exhaustion and a poor quality of life. The purpose of this study was to determine the ratio of work stress and work fatigue using the division of work shifts at Alfamart Tangsi Cikarang. This Alfamart applies 2 work shifts, namely morning and afternoon. This research was conducted by conducting interviews and questionnaires to 4 employees. The work pressure questionnaire uses the OSI-RTM method while the work fatigue uses the 30 Items of Rating Scale. One Way ANOVA was used to test the questionnaire data. The results of the work stress test show a significance level of 0.375 (p>0.05), which means that there is no statistically significant difference in the average work stress between the morning and afternoon shifts. The criterion for the significance of work fatigue is 0.295 (p>0.05), indicating that there is no statistically significant difference in the average level of work fatigue between the morning and afternoon shifts. There is no visible difference in the distribution of shifts at the Tangsi Alfamart location, indicating that the staff does not experience difficulties in dividing the morning and afternoon shifts.